A Bibliometric Analysis of Sustainable Supply Chain Finance Research - Loso Judijanto (West Science Interdisciplinary Studies, 2026)
This study presents a bibliometric analysis of sustainable supply chain finance (SSCF) research to map its intellectual structure, evolution, and emerging trends. By examining a dataset sourced from Scopus and Web of Science, the study employs VOSviewer to visualize keyword co-occurrence, author collaborations, and thematic developments within SSCF literature. The results reveal a significant shift towards integrating financial mechanisms with sustainability goals, with a growing focus on "green finance" and "sustainable finance" linked to environmental objectives. Technological advancements, particularly blockchain and artificial intelligence, are emerging as key tools for enhancing sustainability in supply chains. The analysis highlights the central roles played by countries like India, China, and the United States, while also identifying research gaps, especially in the practical implementation of new technologies and the underrepresentation of developing nations. The study provides insights for future research and practical application in the sustainable supply chain finance domain⁠.